Wnt/β-catenin signaling cell-autonomously converts non-hepatic endodermal cells to a liver fate - So, Juhoon (The Company of Biologists, 2012)
Wnt/β-catenin signaling plays multiple roles in liver development including hepatoblast proliferation and differentiation, hepatocyte differentiation, and liver zonation. A positive role for Wnt/β-catenin signaling in liver specification was recently identified in zebrafish; however, its underlying cellular mechanisms are unknown. Here, we present two cellular mechanisms by which Wnt/β-catenin signaling regulates liver specification. First, using lineage tracing we show that ectopic hepatoblasts, which form in the endoderm posterior to the liver upon activation of Wnt/β-catenin signaling, are derived from the direct conversion of non-hepatic endodermal cells, but not from the posterior migration of hepatoblasts. We found that endodermal cells at the 4–6(th) somite levels, which normally give rise to the intestinal bulb or intestine, gave rise to hepatoblasts in Wnt8a-overexpressing embryos, and that the distribution of traced endodermal cells in Wnt8a-overexpressing embryos was similar to that in controls. Second, by using an endoderm-restricted cell-transplantation technique and mosaic analysis with transgenic lines that cell-autonomously suppress or activate Wnt/β-catenin signaling upon heat-shock, we show that Wnt/β-catenin signaling acts cell-autonomously in endodermal cells to induce hepatic conversion. Altogether, these data demonstrate that Wnt/β-catenin signaling can induce the fate-change of non-hepatic endodermal cells into a liver fate in a cell-autonomous manner. These findings have potential application to hepatocyte differentiation protocols for the generation of mature hepatocytes from induced pluripotent stem cells, supplying a sufficient amount of hepatocytes for cell-based therapies to treat patients with severe liver diseases.